The Relationship between Brand Equity, Customer Satisfaction, and Brand Loyalty on Coffee Shop: Study of Excelso and Starbucks - Susanty, Aries; Kenny, Eirene (ASEAN Marketing Journal, 2021)
This study investigates the effect of the Brand Equity on the Customer Satisfaction and the Brand Loyalty of Starbucks and Excelso coffee shops’ customers. Starbucks is the strongest competitor of Excelso. Data used in this study was primary data which were collected through closed questionnaires with 1-5 Likert scale. A sample of this study was 270 respondents, 135 respondents for each brand. The study used Structural Equation Modelling (SEM) operated by LISREL program to analyze the hypothesis. The results of this study showed that The Physical Quality, the Ideal Self-Congruence, and the Lifestyle Congruence have a positive and significant impact on the Customer Satisfaction on Excelso and Starbucks. Staff behaviour only have a positive and significant impact on the Customer Satisfaction in the Excelso, whereas, brand identification only have a positive and significant impact on the Customer Satisfaction in the Starbucks. However, in both of coffee shop brand, the Consumer Satisfaction have a positive and significant impact on the Brand Loyalty.